If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 + -1(2x + -3) = -6 Reorder the terms: -17 + -1(-3 + 2x) = -6 -17 + (-3 * -1 + 2x * -1) = -6 -17 + (3 + -2x) = -6 Combine like terms: -17 + 3 = -14 -14 + -2x = -6 Solving -14 + -2x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -2x = -6 + 14 Combine like terms: -14 + 14 = 0 0 + -2x = -6 + 14 -2x = -6 + 14 Combine like terms: -6 + 14 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| -2(1-8n)-7(-1+8n)=5 | | 79=4y+15 | | x^-2/3=1/36 | | 2w-14=12 | | 9y+1+10y-13=7x+4 | | 7x+12y=3 | | 14241.9096=81.012*w | | 19y=7x+16 | | (-17)-(2x-3)=-6 | | 8x+6=2+6x | | 7n^2+16n-60=0 | | 6x+7+2x-3=7x+9-2x+7 | | 85+x=85 | | X+10+10=25 | | 3/10*x=2.1 | | g-5g+7-9= | | 5x+6-4x=-17 | | 5x+5=3x-19 | | 8x+6=2+6 | | y=(3)2+5(3) | | 5/x-4=2 | | 2*lnx=3 | | x^2-7x*2x-40=0 | | 11x+2=15(x-2) | | 9(m-4)= | | 30x+45=12x-20 | | 4xy+4xz= | | 7/10x=5.6 | | 13i/2-3i | | x7/10=5.6 | | 2x-24=12-2x | | 25x^3-50x^2-4x+8=0 |